Interstitial lung disease: retrospective study of the prognostic impact of acute exacerbations - Pacheco, Joana; Santos, Ana Isabel; Catarata, Maria Joana; Freitas, Sara (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background: Interstitial lung diseases have high mortality associated with hospitalization for decompensation. There are doubts about the factors involved in the progression of fibrosis, for example the role played by acute exacerbations. With this work, the authors intend to analyze whether there are predictive parameters of mortality related to exacerbations. Methods: A retrospective study was carried out of patients admitted to the Pulmonology department of Coimbra University Hospital Center for exacerbation of fibrosing lung disease between January 2019 and December 2020. These were classified as: idiopathic pulmonary fibrosis (IPF), fibrosing hypersensivity pneumonitis (FHP) and other fibrosing lung diseases. Statistical analysis was performed using SPSS 26.0 considering statistically significant p<0.05 values. Results: The results show that IPF is associated with longer hospital stay in relation to fibrosing HP and other fibrosing lung diseases mean of 20.93 days (95% CI: 14.69-27.18) vs 11.8 days (95% CI: 1.05-17.22, p=0.023) vs 12.23 days (95% CI 2.06-15.34, p=0.007), respectively. Regarding mortality, there was no difference between IPF, PH and other fibrosing diseases (p=0.631). Conclusion: This study demonstrated that IPF, compared to PH and other fibrosing diseases, is associated with longer hospital stays, probably due to its progressive course despite the institution of corticosteroid therapy. As shown in previous studies, it was concluded that there is no difference in terms of mortality between IPF exacerbations and other forms of fibrosing lung disease.